Journey To Hearing: Studi Kasus Perioperatif Nursing Terhadap Implantasi Koklea Pada Anak Penyandang Malformasi Telinga Bawaan - Valentino Febryandy; A. Rizal Fadly (Sabda Abadi Nusantara, 2025)
Background Cochlear implantation is a complex surgical procedure that serves as the primary option for patients with severe hearing impairment due to congenital ear malformations. The main challenges include anatomical variations, higher risks of complications, and the need for specialized perioperative approaches in pediatric patients. This case report aims to document evidence-based perioperative nursing management in a pediatric patient with congenital ear malformation undergoing cochlear implantation. Methods A descriptive case study was conducted using a perioperative nursing care approach based on SDKI, SLKI, and SIKI standards. The subject was a 9-year-old child with Mondini-type ear malformation who underwent unilateral cochlear implantation.DiscussionIn the preoperative phase, interventions focused on physical-psychological preparation, infection prevention (prophylactic antibiotics), and family education. The intraoperative phase involved close monitoring of the facial nerve, management of hypothermia, and the use of straight electrodes for abnormal anatomy. The postoperative phase successfully controlled pain (FLACC scale 3) without complications such as infection or cerebrospinal fluid leakage. The patient was discharged on the second day with a good functional outcome (8/12 responsive electrodes).ResultsA multidisciplinary collaborative approach and evidence-based protocols proved effective in optimizing cochlear implantation outcomes in congenital malformations. Family education and close monitoring of complications were key factors in the success of the procedure.